2000
DOI: 10.1366/0003702001949393
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multivariate Analysis to Determine Temperature from Low-Resolution Infrared Spectra of Carbon Dioxide

Abstract: The remote optical monitoring of gaseous contaminants is important for both military and industrial applications. An important parameter for quantifying chemical species and for predicting plume dynamics is the temperature. While in some industrial monitoring situations it may be practical to independently measure the temperature of stack emissions, for compliance monitoring and military chemical reconnaissance a remote optical means of estimating gas plume temperature is required. It was noticed that the band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Previous work by Gary Small et al 4 and Szczepanski et al 5 has shown that the determination of plume concentration by passive-remote IR sensing is highly dependent on temperature. Even though the filament reached temperatures at or above 500 8C, the pressures and temperatures of the generated gases were small.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work by Gary Small et al 4 and Szczepanski et al 5 has shown that the determination of plume concentration by passive-remote IR sensing is highly dependent on temperature. Even though the filament reached temperatures at or above 500 8C, the pressures and temperatures of the generated gases were small.…”
Section: Resultsmentioning
confidence: 99%
“…After the calibration measurements a calibration model is constructed, which is then used for determining the content of the tested substances. This method can also be used to determine temperature, but only to a very limited extent [13]. Conditions applicable to the empirical calibration measurements in emission spectroscopy are achieved only for very short measurement paths [14].…”
Section: Introductionmentioning
confidence: 99%